The Influence of Job Involvement on Organizational Commitment in BJB Cimahi - Sari, Ajeng Purnama; Sojanah, Janah (Entrepreneurship Faculty, Universitas Garut, 2023)
For an organization to have a competitive advantage, it requires continuous employee commitment Employees who arecommitted to the organization have a tendency to remain in the organization. The loss of employee organizational commitment means theorganization loses support and loyalty from employees in achieving organizational goals. This research was conducted to find out howmuch influence job involvement has on organizational commitment.The design used in this research iscross sectional method. This type ofresearch uses verification methods explanatory survey. The sampling technique used is a non-probability sampling technique withsaturated samples as the sampling technique. The number of samples studied was 54 people. The data analysis technique used isPartialLeast Squares (PLS) using the smartPLS computer software program version 3.0. Based on the research results, show that jobinvolvement influence on organizational commitment.